Frantz Fanon's Contribution to Hegelian Marxism. (September 2017) - Hudis, Peter
Although Frantz Fanon's work has been widely read and discussed in recent years, his contributions are often abstracted from its debt to Marxist theory and Hegelian philosophy. This paper seeks to correct this by re-examining his approach to issues of recognition, identity, and self-consciousness in Black Skin, White Masks in light of contemporary issues of racism and ethnic identity. Fanon departs from Hegel in many respects, especially concerning his understanding of the nature of the 'master/slave' relations that are structured along racial lines. He also seeks to go beyond Marx by providing a psycho-affective as against a primarily economic analysis of exploitation and alienation. Instead of representing a departure of the dialectical tradition, however, Fanon's insights on these and other issues represent a crucial extension and concretization of it in light of the realities of his lived experience.